LAND SURVEY REGARDING RECONSTRUCTION OF SÄ‚LIșTE TAILING DUMP - P.I. Plesa; M. Dirja (Agricultura, 2013)
Classification of polluted soils in Romania is made by classes, types and degrees of pollution. Existing legislation in Romania includes some zoning laws with respect to the protection, conservation and sustainable use of soil resources with articles that are poorly correlated and largely inappropriate to question the use and protection of the soil, at the current pace accelerated degradation of the landscape, mode of agricultural use of slopes and new requirements of the European Union. The main power source of groundwater on the project site is rainwater. Sites (SÄƒliște dump, dump Gura Rosia respectively TMF Åžesei Valley ) is located in an area classified as a temperate continental climate with strong topographic influences.